EKSPLOITASI SUMBER DAYA ALAM VERS S PERLINDUNGAN SUMBER DAYA BUDAYA Dl PEGUNUNGAN MERATUS - Nuralang, Andi (Naditira Widya, 2007)
South Kalimantan's Watertower in Meratus mountain range. If Maratus hreak, it territory will inundated. The people is a part included have relationship balancing accordance or dropped and balance of interaction. From all the creature, the people can interaction. While it intervention with high intensity with included although ecosystem resuit disturbed b&lancing ecology until inundated. If explitation wish be aware important realm. Return Meratus's harmoniously cannot delay, if will become prosperity south Kalimantan from calamity and destitute. The fact calamity to the amount territory result disturbed forest in mountain. Be lust forest meaning will be lost inundated people and it culture.